Taxonomic review of the genus Pseudocaissa Solovyev & Witt, 2009 (Lepidoptera: Limacodidae), with description of a new species from Prov. Yunnan, China - Wu, Jun; Han, Hui-Lin (Zootaxa, 2025)
The third species of the genus Pseudocaissa Solovyev & Witt, 2009, P. yutua sp. nov., is described from northeastern Yunnan Province, China. The new species closely resembles its congeners, P. apiata Solovyev & Witt, 2009 and P. marvelosa (Yoshimoto, 1994), but is distinguished primarily by distinct differences in the male genitalia. Images of male adults and genitalia, as well as a key to Pseudocaissa species and their distributions, are presented.